2017
DOI: 10.1097/ppo.0000000000000281
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetics and Precision Oncology

Abstract: Epigenetic alterations such as DNA methylation defects and aberrant covalent histone modifications occur within all cancers and are selected for throughout the natural history of tumor formation with changes being detectable in early onset, progression and, ultimately, recurrence and metastasis. The ascertainment and use of these marks to identify at-risk patient populations, refine diagnostic criteria, and provide prognostic and predictive factors to guide treatment decisions is of growing clinical relevance.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(56 citation statements)
references
References 66 publications
1
54
0
1
Order By: Relevance
“…It is known that tumor aneuploidy (chromosome number variation) and genetic heterogeneity/diversity can influence the disease behavior including metastatic capability [190192]. Apart from genetic changes, epigenetic alterations such as DNA methylation and histone modifications could play a significant role in metastasis [193,194]. Accumulating evidence suggests that both genetic and epigenetic changes can occur in obesity [195199].…”
Section: Leptin In Tumor Progressionmentioning
confidence: 99%
“…It is known that tumor aneuploidy (chromosome number variation) and genetic heterogeneity/diversity can influence the disease behavior including metastatic capability [190192]. Apart from genetic changes, epigenetic alterations such as DNA methylation and histone modifications could play a significant role in metastasis [193,194]. Accumulating evidence suggests that both genetic and epigenetic changes can occur in obesity [195199].…”
Section: Leptin In Tumor Progressionmentioning
confidence: 99%
“…Preclinical studies suggested that both gene mutation and epigenetic inactivation of BRCA1 by promoter hypermethylation can cause protein down-regulation and subsequent sensitivity to PARP (Poly-ADP-ribose polymerase) inhibition [73,74]. Also, it is recognized that aberrant DNA methylation and changes in gene expression are correlated with the molecular subtypes of BC [9,75]. However, epigenetic studies in IBC are scarce.…”
Section: Epigenetic Alterations In Inflammatory and Non-inflammatory mentioning
confidence: 99%
“…DNA methylation-based biomarkers are useful tools to be applied in cancer diagnosis and prognosis. They are also associated with the therapeutic response and guide treatment decisions for cancer patients [22,23].…”
Section: Introductionmentioning
confidence: 99%